2006
DOI: 10.1083/jcb.200605074
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic cohesins modulate chromosome compaction during meiotic prophase in fission yeast

Abstract: The meiotic cohesin Rec8 is required for the stepwise segregation of chromosomes during the two rounds of meiotic division. By directly measuring chromosome compaction in living cells of the fission yeast Schizosaccharomyces pombe, we found an additional role for the meiotic cohesin in the compaction of chromosomes during meiotic prophase. In the absence of Rec8, chromosomes were decompacted relative to those of wild-type cells. Conversely, loss of the cohesin-associated protein Pds5 resulted in hypercompactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
141
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(162 citation statements)
references
References 60 publications
21
141
0
Order By: Relevance
“…38,39 For mitotic chromosomes this number is estimated to be 3,000-2,00,000 in vertebrates [39][40][41] but only 140 in S. cerevisiae 32 and 700 in S. pombe. 42 Thus, the degree of chromosome compaction in mitosis compared to interphase rises dramatically in higher eukaryotes. Although it is generally believed that maximal chromosome condensation is achieved in metaphase when chromosomes line up on the metaphase plate, this view has been challenged recently.…”
Section: Regulation Of Chromosome Segregation In Anaphasementioning
confidence: 99%
“…38,39 For mitotic chromosomes this number is estimated to be 3,000-2,00,000 in vertebrates [39][40][41] but only 140 in S. cerevisiae 32 and 700 in S. pombe. 42 Thus, the degree of chromosome compaction in mitosis compared to interphase rises dramatically in higher eukaryotes. Although it is generally believed that maximal chromosome condensation is achieved in metaphase when chromosomes line up on the metaphase plate, this view has been challenged recently.…”
Section: Regulation Of Chromosome Segregation In Anaphasementioning
confidence: 99%
“…In vegetative cells, mitotic cohesin containing Rad21 and Psc3 is preferentially enriched across heterochromatin domains including at centromeres, and shows distinct peaks at specific sites on chromosomal arms 5,6,9,21 . As cells enter meiosis, Rec8-Rec11 replaces Rad21-Psc3 on arms, while Rec8 partners with Psc3 at centromeres 22,23 . Interestingly, we found that Rec8 and its interaction partner Rec11 were loaded onto chromosomal arms in mmi1 ∆ cells, at sites normally occupied by mitotic cohesin (Extended Data Fig.…”
mentioning
confidence: 99%
“…The distributions of the nucleosomes and the binding sites of DNA-associated proteins differ substantially among the 1st, 2nd, and 3rd chromosomes in S. pombe [14,15], since they are highly dependent on DNA sequences that show vast variation among the three chromosomes. In general, the distributions of the nucleosomes and DNA-associated protein-binding sites determine the higherorder physical structure of chromatin [14][15][16].…”
Section: Assumptions Of the Modelmentioning
confidence: 99%
“…In general, the distributions of the nucleosomes and DNA-associated protein-binding sites determine the higherorder physical structure of chromatin [14][15][16]. This fact suggests that homologous chromosomes are structurally similar, whereas the structures of non-homologous chromosomes differ greatly.…”
Section: Assumptions Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation